Reposition the School Management Strategic at SD IT Riyadhoturrohman - Wahyu Fitrina Defi (Sean Institute, 2022)
Quality in a school is becoming a priority for the public especially parents and students. Many aspects that can being indicator of a school quality for public, they are may be facilities, curriculum, the result that the student got after studying, a culture, leadership, coordination, and many else. We can named all the aspects as a school management strategic. Of course, we can observing at many school, there is no school will be perfect in practising the strategic. Sometimes some aspects good, and no for the other aspects. It’s the case at SD IT Riyadhoturrohman. The aim of this research is for describing some strategic that the principal do for reposition the school management becoming the good quality. The data was collected from the primary and secondary data. The techniques that used by qualitative method, that are interview, observing, and documentation study then combine some literature that have relation with the topic. The data was analyzed by data reduction, data presentation, and take some conclusion. The result of this research are: 1) The role of the principal is a major player in the repositioning of school management, 2) school management repositioning is carried out on aspects: curriculum and teaching programs, educators and education staff, students, finance, facilities and infrastructure, school relations with the community, and special services.